Self-reported food intolerance, dietary supplement use and malnutrition in chronic inflammatory bowel diseases: Findings from a cross-sectional study in Lebanon. - Maha Hoteit; Nour Ftouni; Malak Olayan; Souheil Hallit; Joya Maria Karam; Mahmoud Hallal; Samer Hotayt; Bilal Hotayt (PLoS ONE)
Background/aims Chronic inflammatory bowel diseases (IBDs), including Crohn's disease and ulcerative colitis are known for a combination of food intolerance, decreased oral intake, and malabsorption which all predispose patients to malnutrition and suboptimal dietary intake. The present study was conducted to 1) examine self-reported food intolerances and dietary supplement use 2) assess nutritional intake 3) assess the nutritional status and screen for malnutrition among patients with chronic inflammatory bowel disease (CIBD). Methods 48 patients with CIBDs (28 Crohn's disease, 15 ulcerative colitis and 7 with atypical forms of IBD) took part in this cross-sectional study. Participants completed a food frequency questionnaire targeting dietary intakes and food trends over time. A questionnaire about food intolerance was also used. The nutritional status of patients with CIBDs was evaluated by a detailed history (medical diagnosis and medications and supplements administered) and by using the subjective global assessment (SGA) tool. Anthropometric data including height, weight, and BMI with body composition assessment using automated scales and stadiometer, while Bio-impedancemetry was used to measure body fat and visceral fat. Statistical analysis was conducted using SPSS 27, employing mean values, standard deviations, absolute and relative frequencies and Pearson's chi-square test, with significance set at p ≤ 0.05. Results Food intolerance was equally common in all the types of CIBD specifically for dairy products, spicy foods, and high-fiber food items (beans and raw vegetables). Individuals with CIBD were also complaining about meat and chicken products (68%), followed by alcohol and soda (64%) and fish and sea foods (59%). 17% of the patients were malnourished. A significant percentage of malnourished patients with CIBD had to follow a diet outside the flare, had a nutritional follow up, were currently taking corticosteroids and had a severe form of the disease compared to patients who were well nourished. Conclusions This study has contributed valuable insights into the understanding that some food items could be associated to periods of increased disease activity in CIBD patients and that awareness/intervention regarding nutrition must be provided by healthcare professionals (dietitians, physicians…) to decrease the need for second line therapy. In addition, this self-reported food intolerance paper gives an insight for patients on food items usually avoided by CIBD patients during flares.